A success journey of Mehmet Oz in cardiothoracic surgery - Afdzaluddin, Atiqah (IIUM Press, 2011)
Muslim scientists have a lot of contributions in many areas such as medical, engineering, pharmaceutical and architectural. Many do not fully appreciate the numerous scientific contributions Islamic civilization and the early Muslims made. From the reality, the Muslim youth generations were raised by Western scientific ideological and not instill their thinking with the achievement by Muslim scientist. The pioneer in medical field such as Ibn Sina, AI-Kind, AI-Zahrawi, are the famous name in the early area. As far as we concern, their theories and ideology coincidently contribute to the development of medical theories. Not to be forgotten the contribution of Muslim scientist nowadays is the achievement as Muslim ummah will encourage youth generation in achieving their ambition as well as bringing the uphold name ofMuslim throughout the wor